PENYULUHAN MENGGUNAKAN METODE CERAMAH DENGAN MEDIA SLIDE TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG PREMENSTRUAL SYNDROME (PMS) - N, Lili Eky Nursia; Dary, Sry Wulan; Duana, Maiza; Nabela, Danvil (Jurnal Maternitas Kebidanan, 2024)
Premenstrual Syndrome (PMS) is a symptom that occurs before the menstrual period and will stop when menstruation begins. The low knowledge of young women about PMS can cause many PMS complaints. One strategy to increase knowledge through counseling is using the lecture method with slide media.The purpose of this study was to determine differences in counseling using the lecture method with slide media on young women's knowledge of Premenstrual Syndrome (PMS) at Serambi Mecca Islamic High School, West Aceh. This type of research uses quasi-experimental with one group pretest-posttest design. The population in this study were all young women at Serambi Mecca Islamic High School, West Aceh, totaling 221 students. Determination of the number of samples using the slovin formula as many as 147 samples. The sampling technique used stratified random sampling. Data analysis was performed by means of univariate analysis and bivariate analysis using the Wilcoxon test with SPSS. The research instrument used a questionnaire. The results of this study indicate that there is a significant effect of providing counseling using the lecture method with slide media on respondents' knowledge about Premenstrual Syndrome (PMS), obtained Pretest–Posttest 1 knowledge with a Pvalue of 0.000 and Posttest1–Posttest2 with a Pvalue of 0.008 which is smaller than the value α = 0.05. The conclusion of this study is that there is a difference in increasing the knowledge of female students before, after, and after 10 days of being given counseling using the lecture method with slide media. It is hoped that future researchers can use the lecture method with slide media as a reference in collaborating with health agencies to empower reproductive health so as to increase student knowledge. Keywords : Premenstrual Syndrome, PMS, Lecture Method